2009
DOI: 10.1606/1044-3894.3842
|View full text |Cite
|
Sign up to set email alerts
|

The Experiences of Minority Immigrant Families Receiving Child Welfare Services: Seeking to Understand how to Reduce Risk and Increase Protective Factors

Abstract: Wide recognition that families in the child welfare system experience multiple stressors has resulted in the development of a range of prevention and intervention strategies at individual, family, and policy levels.1 This article reports on a research study with minority immigrant families. The aim was to understand stressors they perceived as contributing to child welfare interventions, and services they found helpful or unhelpful. Using the conservation of resource (COR) theory, the findings highlight the er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 21 publications
1
64
0
1
Order By: Relevance
“…16,17,22,26 Most parents reported experiencing difficulties because they did not speak the local language. 25,27,32,33 In terms of family structure, the majority of immigrant children involved with CPS lived in two-parent households (mostly with both biological parents), in which the parents were either married or living with a common-law partner. [14][15][16][17][18]22,31,32 Only six studies investigated the link between these characteristics and the likelihood of maltreatment occurring.…”
Section: Microsystemic Risk Factors For Child Maltreatmentmentioning
confidence: 99%
See 4 more Smart Citations
“…16,17,22,26 Most parents reported experiencing difficulties because they did not speak the local language. 25,27,32,33 In terms of family structure, the majority of immigrant children involved with CPS lived in two-parent households (mostly with both biological parents), in which the parents were either married or living with a common-law partner. [14][15][16][17][18]22,31,32 Only six studies investigated the link between these characteristics and the likelihood of maltreatment occurring.…”
Section: Microsystemic Risk Factors For Child Maltreatmentmentioning
confidence: 99%
“…Immigrant families may also experience difficulties related to work conditions, such as professional deskilling or poor work conditions. 25 Finally, six studies reported that immigrant families involved with CPS had low to no social support, 25,31 but the link between social isolation and increased risk of maltreatment was not significant. [16][17][18]22 Protective Factors Specific to Immigrant or Refugee Families…”
Section: Exosystemic Risk Factors For Child Maltreatmentmentioning
confidence: 99%
See 3 more Smart Citations